Analisis Tingkat Kepuasan Nasabah dalam Menggunakan Automatic Teller Machine (ATM) Pada PT. Bank Muamalat Indonesia Cabang Gorontalo - Rudiyanto, Rudiyanto; Syawaluddin, Syawaluddin (Madani: Jurnal Pengabdian Ilmiah, 2020)
The purpose of this study is to determine how the level of the level of customer satisfaction nights using Automatic Teller Machine (Atm) at PT. Bank Muamalat Indonesia, Gorontalo Branch . This study has a problem limitation for Bank Muamalat ATM users. This study uses a qualitative approach to data collection techniques, observation, interviews, documentation. Based on the research results of PT. Bank Muamalat Indonesia, Gorontalo BranchRegarding customer satisfaction with the facilities provided by employees, it is quite good, seen in the suitability of customer expectations at ATM facilities, interested in returning to the facilities provided and the willingness of customers to visit again, this is done by Bank Muamalat to maintain the loyalty of its customers by providing good service facilities to customers, but there are some ATM facilities poorly visible lack of facilities and infrastructures that are not functioning properly and the location where y ang less strategy.